PEMETAAN POSISI KEUNGGULAN EKOWISATA BEE JAY BAKAU RESORT - Mochammad Fattah; Candra Adi Intyas; Tiwi Nurjannati Utami; Dwi Sofiati; Kartika Intan Abdillah (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Bee Jay Bakau Resort (BJBR) is one of the main tourist destinations in Probolinggo City that utilizes the mangrove ecosystem. The study aims to analyze the advantages position mapping of BJBR. The study uses correlational approach with accidental sampling of 70 respondents. Data were analyzed by using exploratory factor analysis (EFA) and correspondence analysis (CA) with 16 attributes. This study assessed three mangrove ecotourism sites in East Java. The main factors that influence tourists visiting BJBR are tourist attractions, prices, tourism completeness and safety, mangrove preservation, as well as service friendliness. BJBR has tourism advantages in the form of complete facilities and completeness of its attractions. Meanwhile, the advantages of Wonorejo Surabaya mangrove ecotourism are among others: the availability of education related to mangroves and the cleanliness of the facilities. On the other side, The Clungup Mangrove Conservation Malang has the advantages in the form of mangrove conservation, tourism beauty, tourism memories, and tourism safety. BJBR managers need to improve the sustainability of the mangrove forest ecosystem and educational facilities regarding the benefits of mangroves in order to have a positive impact on tourists.